DNA and Protein-Based Methods for Halal Gelatin Authentication: A Review - Nurul Azizah; Welly Anggraini (Jurnal Pijar MIPA, 2026)
Tracing and tracking halal has emerged as an imperative for Muslim consumers worldwide to ensure that the meat-based products comply with Islamic law and food safety standards. The most challenging technical issue in halal authentication concerns products derived from gelatin. Because extreme manufacturing processes, such as high-temperature and chemical processing, damage the physical and molecular architecture of raw materials, detection is difficult. Objective: This study builds on a systematic literature review with a PRISMA protocol to map DNA- and protein-based detection techniques and compare their efficiencies. Methods: A systematic search was conducted across major databases, including Google Scholar, ScienceDirect, and ResearchGate, for peer-reviewed articles published from 2015 to 2025. From this process, 25 studies with high-impact potential were selected for thematic analysis. The results show that DNA-based methods dominate the literature (80%). Despite this, quantitative PCR (qPCR) remains the "gold standard" owing to its specificity and sensitivity. However, the findings reveal that droplet digital PCR (ddPCR) can detect highly degraded DNA in complex matrices, whereas traditional methods have shown limitations for detecting DNA in pharmaceutical capsules and cosmetics. On the other hand, protein-based methods such as ELISA remain useful for fast, economical screening, but sensitivity is substantially reduced at higher processing temperatures. In conclusion, this study highlights the importance of combining IPC and multi-method frameworks to limit false negatives. The findings of this study are substantial enough to provide the fundamentals for the alternative scaling-up of halal assurance systems, especially in the form of guidelines that provide a scientific framework for strengthening a more reliable authentication system for processed gelatin products, at least within Indonesia.